PENGARUH REPUTASI KAP DAN KOMPLEKSITAS AUDIT TERHADAP AUDIT DELAY - Inggit Pramudita; Endang Sri Utami (Value : Jurnal Manajemen dan Akuntansi, 2023)
The deadline for submitting audited financial reports has been set by the government, but the delay in submitting these reports has increased. This delay is known as audit delay. The study aims to show that Public Accounting Firms (KAP) reputation and audit complexity have an influence on audit delay in companies listed on the Indonesia Stock Exchange. Quantitative methods are used to test hypotheses. The population of this research is consumer cyclicals, properties & real estate, energy, consumer non-cyclicals, industrial, basic materials, and infrastructure companies listed on the Indonesia Stock Exchange as the population.  The research used purposive sampling technique to produce a sample of 18 companies during 2020-2021. The data was analyzed using multiple linear regression analysis which was previously carried out by descriptive statistic tests and classical assumption test. The results found by researchers are that Public Accounting Firms (KAP) reputation has a negative effect on audit delay, while audit complexity has no effect on audit delay. From this research, public accounting firms can pay more attention to their auditors by providing training opportunities so that their experience, knowledge and professionalism are maintained and / or increased so that the reputation of KAP is maintained or increased. Keywords: Reputation of A Public Accounting Firm, Audit Complexity, Audit Delay